Objektifikasi Perempuan pada Hasil Pencarian “Pin-Up Tattoo” di TikTok: Analisis Wacana Sara Mills - Chiara Ifani Mukti; Fikih Bintang Anggara (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the objectification of women in the visual representation of pin-up tattoos on TikTok using a qualitative approach based on Sara Mills’ Critical Discourse Analysis framework. The data consisted of three visual content samples obtained from the keyword search “Pin-Up Tattoo” on TikTok, analyzed through three main elements: body exploitation, revealing clothing, and female character facial expressions. The findings reveal that women are consistently positioned as passive objects through body fragmentation, sexualized attributes, and expressions representing submission. Meanwhile, male tattoo owners and visual producers occupy the subject position by controlling the meaning of representation. The study demonstrates that pin-up tattoos function as a medium for reproducing the male gaze, reducing women into visual commodities. Furthermore, TikTok intensifies this process through massive content circulation, making objectifying representations increasingly normalized within digital culture.